Prediction for swelling deformation of fractal-textured bentonite and its sand mixtures in salt solution. (29th May 2019) - Xiang, Guo-sheng; Yu, Feng; Xu, Yong-fu; Fang, Yuan; Xie, Sheng-hua
Abstract: Swelling deformation tests of Kunigel bentonite and its sand mixtures were performed in distilled water and NaCl solution. The salinity of NaCl solution has a significant impact on the swelling properties of bentonite, but not on its surface structure. The surface structure was characterized using the fractal dimension D s . Based on the fractal dimension, a unique curve of the e m – p e relationship ( e m is the void ratio of montmorillonite and p e is the effective stress) at full saturation was introduced to express the swelling deformation of bentonite–sand mixtures. In mixtures with a large bentonite content, the swelling deformation always followed the e m – p e relationship. In mixtures with a small bentonite content, when the effective stress reached a threshold, the void ratio of montmorillonite e m deviated from the unique e m – p e curve due to the appearance of a sand skeleton. The threshold of vertical pressure for mixtures in different solutions and the maximum swelling strains were estimated using the e m – p e relationship. The good agreement between estimates and experimental data suggest that the e m – p e relationship might be an alternative method for predicting the swelling deformation of bentonite–sand mixtures in salt solution.